Oedipus Riddles - Preložnik, Andrej; Nestorović, Aleksandra (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
The paper discusses an interesting group of glass intaglios with the motif of Oedipus and the Sphinx. They are known from sites between the Adriatic, the Danube and the Black Sea, and occur in various colors and cuts, which suggests production in different molds or even workshops. Probably modeled on an intaglio made in an Italian officina gemmaria, the glass replicas may have been produced at Aquileia. The style points to the Late Republican or Augustan era, whereas the material of the glass copies and the funerary context from Aquincum show they were in use and probably produced till the 4 th century. The paper also discusses the possible meanings of the motif, from a simple illustration of the famous heroic adventure to a metaphoric depiction representing the mystic message of the key to a blessed afterlife.